Effect of plant growth regulator and explant type on callus induction of Moringa Oleifera - Oyebisi, Ayooluwa Oyetoro, 1985-, author; Alina Wagiran, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Sains (Bioteknologi)) - Universiti Teknologi Malaysia, 2017